MHD mixed convection and heatlines approach of nanofuids in rectangular wavy enclosures with multiple solid fns - Fatin M.Azizul, Fatin M.Azizul; Ammar I.Alsabery, Ammar I.Alsabery; Ishak Hashim, Ishak Hashim; Roslan, Rozaini; Habibis Saleh, Habibis Saleh (2023)
Two dimensional wavy walls rectangular cavity with inclined magnetohydrodynamic has been examined in mixed convection confgurations. Triple fns arranged in the upwards ladder were flled within alumina nanoliquid in the cavity. Vertical sinusoidal walls were heated, and the other side was kept cold while both horizontal walls were kept adiabatic. All walls were motionless except the top cavity that was driven to the right. The diversifed range of control parameter in Richardson number, Hartmann number, number of undulations, length of the cavity has been performed in this study. The analysis was simulated using fnite element method by employing the governing equation formula, and the results were delineated in the form of streamlines, isotherms, heatlines, and comparisons on several relationships between the local velocity in the y-axis line of 0.6, local and average Nusselt number along the heated surface and dimensionless average temperature. The fndings revealed that high concentration nanofuids boost the rate of heat transfer without the need to apply any magnetic feld. Results found that the best heat mechanisms are natural convection with signifcant-high Richardson number as well as constructing two waves on the vertical walls in the cavity.